Host factors associated with respiratory particle emission and virus presence within respiratory particles: a systematic review - Horstink, Nils; Lassing, Kirsten; Knoester, Marjolein; Vermeulen, Lucie C.; Rossen, John W. A.; Voss, Andreas; Lokate, Mariëtte (Frontiers in Microbiology, 2025)
IntroductionUnderstanding host factor-related mechanisms that drive variability in respiratory particle emission and virus presence in exhaled particles is essential to assess transmission risk and potentially identify individuals with elevated infectiousness.MethodsWe conducted a systematic review of human observational studies examining associations between host factors and either respiratory particle emission or virus presence in exhaled particles. Searches in PubMed, EMBASE, and Web of Science covered studies up to September 2024. Risk of bias was assessed using STROBE-based criteria. Findings were synthesized narratively, grouped by host factor and outcome type.ResultsForty-four studies met inclusion criteria: 34 assessed host factors in relation to particle emission, and 11 examined viral presence in exhaled particles. Fine particle emission (<5 μm) was most consistently associated with older age (n = 16), physical exercise (n = 6), and active infection (n = 6). No consistent associations were found for sex (n = 21), body mass index (BMI; n = 10), or smoking (n = 6). Viral presence—mainly influenza and SARS-CoV-2—was more strongly associated with time since symptom onset (n = 8) and lower respiratory symptoms (n = 3), based largely on genomic detection. Associations with other factors, including upper respiratory symptoms (n = 6), swab viral load (n = 11), age (n = 6), sex (n = 6), and BMI (n = 2), were inconsistent or absent. Physical exercise was not evaluated in relation to viral presence.DiscussionFine respiratory particles (<5 μm) were the predominant size fraction detected and often contained higher concentrations of viral RNA. Age, physical exercise, and active infection were consistently associated with increased emission of these particles. The presence of respiratory viruses in exhaled air was more strongly linked to infection-related factors such as early symptom onset and lower respiratory involvement. These patterns suggest distinct mechanisms contributing to airborne transmission. Interpretation was limited by methodological heterogeneity and predominant reliance on PCR. Still, consistent associations with host factors suggest their potential as indicators for transmission risk. As evidence focused mainly on influenza and SARS-CoV-2, generalizability is limited. Standardized methods and further research are needed to strengthen outbreak preparedness.